IMPLEMENTATION OF DEMONSTRATION METHOD BASED ON THE WORLDBOARD MEDIA TO IMPROVE SPIRITUAL AND MUSICAL INTELLIGENCE (Study in Group B PAUD PKK Talang Tinggi District of Seluma) - Saprida Sisanti; Alexon Alexon (UNIB Press, 2018)
The purpose of the study was to describe the application of demonstration methods in improving spiritual and musical intelligence of early childhood based on joyful board media in group B in PKK talang Tinggi ECD Seluma District. This study used Clasroom Action Research (CAR). The subjects of this study were 15 children in group B1 in PKK Talang Tinggi Seluma District. The data collection techniques used a child’s observation sheet on spiritual and musical intelligence. Analysis of researcd data used mean and T test. The results of the study show that children’s musicality in cycles 1,2 and 3. The results of this study show that teacher has successfully implemented this method, furthermore, this method can scientifically spiritual and musical intelligence. The results of this study recommend that joyful board media is one of the media that can be done by teachers to improve spiritual and musical intelligence